Consequential damage and the legal basis for a claim for compensation for it (An analytical study in Iraqi civil law) - Mohammed Hanoun Jafar; Zubeir Mustafa Hussein (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Civil responsibility, especially that that is arising from illegal acts is generally essential in various civil laws. Among topics related to this kind of responsibility are illegal acts that affect the human being physically. For instance, acts that cause damages to people such as injuries and in the worst case killing or death. Although Iraqi Civil Code depended on the Islamic Jurisprudence in regulating rules of civil responsibility concerning illegal acts, it did not adopt rules of compensation based on Islamic law for such actions. It adopted rules of compensation from other civil law especially, Egyptian Civil Law. Such rules included the right to compensation for persons that are related to the dead person. The Iraqi Civil Law provides for the right to compensation for those who incur damages, physical or mental, as a result of the death of the victim who faced the illegal act in Articles 202-205.This study concentrates on this type of injury and those who are entitled to compensation in such Articles mentioned above. Such persons include the wife of the deceased person and his/her close relatives. In addition, it includes those people who were dependent on the deceased person and his death led to the interruption of such support. This study tries to determine the type of damage they incur, its characteristics and conditions, and distinguishing the lawsuit for getting such compensation from other inheritance-related lawsuit. It also covered the basis of the lawsuit for compensation through analytical approach to the texts of the Iraqi Civil Law. This study reached several conclusions and recommendations. The most important one is defining the damage as secondary damage instead of naming it reversed damage. Further, the basis of the compensation is law provisions instead of illegal acts. Finally, we suggest that the Iraqi lawmaker adopt the compensation rules or the guarantee that is provided by Islamic law with respect to illegal acts conducted against human beings.